IMAGING EVALUATIONS OF UNICA CERAMICS UNDER THERMAL CYCLE CONTROL CONDITIONS - Raluca Todor; Emanuela Lidia Crăciunescu; Marius Manole; Andreea Codruţa Novac; Daniela Maria Pop; Alina Doina Tănase; Cosmin Sinescu; Andrei Mostovei; Florin-Ionel Topală; Mihai Romînu; Meda-Lavinia Negruţiu (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study: To evaluate the efficacy of Optical Coherence Tomography (OCT) in non-invasively monitoring temperature variations during ceramic sintering for dental prosthetics, emphasizing the importance of precise temperature control for optimal material properties and structural integrity. Materials and Methods: The study utilized OCT to examine 17 metal-ceramic restorations at various sintering temperatures (standard, 80°C below, and 50°C above the standard). The method involved generating 61 cross-sectional images per prosthesis to identify defects and structural changes. Results: OCT revealed significant insights into the impact of temperature deviations on ceramic microstructure, including uniform grain sizes at standard temperatures and areas of reduced retention at elevated temperatures, highlighting the technology's potential in quality control. Conclusions: OCT offers a rapid, accurate, and non-destructive means to assess sintering temperatures and detect defects in dental ceramics, facilitating improvements in dental prosthetics' fabrication process. The study advocates for OCT's integration into routine dental laboratory practices to enhance prosthesis quality and reliability.